Trade Issues in East Asia, January 2008 : Overcoming Trade Barriers from Standards and Technical Regulations - World Bank (Washington, DC, 2014)
This paper is about trade issues in East Asia. One of the most important non-tariff measures is regulations and standards aimed at securing the safety and or quality of products, labeling requirements and protection of the environment. Standards are now recognized as a trade issue since they determine market access. The use of standards by governments to meet public health and safety objectives and by the private sector to meet market-driven consumer and industrial objectives is important for economic development. Standards provide information on the quality and reliability of a product that may not be readily observable and thus reduce uncertainty and contribute to increased trade. Standards have become a key element in facilitating trade within and between countries since in order for a good to be traded it must comply with the agreed standard. This applies to both mandatory standards required by governments and voluntary standards set by industry associations and other non-state actors. Recognizing the potential of diverging national technical regulations to hinder trade flows, the Association of South-East Asian Nations (ASEAN) has taken steps to eliminate such barriers in the sectors it considers important for economic integration. The sector that will be the first to have a fully harmonized regulatory regime across ASEAN countries will be cosmetics, starting in January 2008. The new regulation primarily involves broadly defined common safety requirements and a new approach to risk management, which does away with the requirement of pre-market approval for cosmetics products and introduces instead a system of post-market surveillance. In doing so, the new directive shifts to a great extent the responsibility of ensuring safety from the government to the private sector.